1984
DOI: 10.1007/bf01852390
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study with various anesthetics in mice (pentobarbitone, ketamine-xylazine, carfentanyl-etomidate)

Abstract: The following three regimens of anesthesia in mice were compared: (1) Ketamine 100 mg--xylazine 5 mg/kg b.wt. i.m., (2) pentobarbitone 50 mg/kg b.wt. i.p., and (3) carfentanyl 0.003 mg--etomidate 15 mg/kg b.wt. i.m. For these dosage rates the respiratory variables, i.e., respiratory rate, paO2, paCO2, pHa, BEa, HCO-3a, and the circulatory parameters, i.e., heart rate, mean arterial pressure and hematocrit, were determined during the conscious state, during surgical anesthesia, and at waking time. With ketamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 10 publications
11
67
0
2
Order By: Relevance
“…In rats, in vivo recordings of RTN neurons were performed under pentobarbital, urethane, ketamine, or halothane anesthesia aiming primarily to study the comparative response to nociceptive stimuli in RTN and in the ventroposterior lateral nucleus of the thalamus (Yen and Shaw, 2003). Various general anesthetics were compared in rats (Field et al, 1993) and mice (Erhardt et al, 1984). The combination of ketamine and xylazine might be considered the most reliable for anesthesia of mice, despite that respiration was moderately decreased and the cardiovascular system was strongly depressed.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, in vivo recordings of RTN neurons were performed under pentobarbital, urethane, ketamine, or halothane anesthesia aiming primarily to study the comparative response to nociceptive stimuli in RTN and in the ventroposterior lateral nucleus of the thalamus (Yen and Shaw, 2003). Various general anesthetics were compared in rats (Field et al, 1993) and mice (Erhardt et al, 1984). The combination of ketamine and xylazine might be considered the most reliable for anesthesia of mice, despite that respiration was moderately decreased and the cardiovascular system was strongly depressed.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know the mechanism by which pentobarbital anesthesia stabilizes and improves breathing in adult Mecp2-/y mice. It is known that this anesthetic depresses cerebral metabolism (Steen and Michenfelder, 1979) and resting respiration (Erhardt et al, 1984). Pentobarbital anesthesia is also affected by noradrenergic agents (Dessaigne et al, 1976;Ojima et al, 1995;Dalley et al, 1998), and other anesthetics have been shown to alter the activity and excitability of central NE neurons (Clement et al, 1998;Hirota and Kushikata, 2001) and to decrease mRNA levels of NE transporters (Hara et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to discuss whether the absence of modification in the firing synchronicity that we observed between pairs of RTN cells in PVKO with respect to WT is due to the anesthetized preparation. In a comparative study of the effects of various general anesthetics in mice, it was indicated that the combination of ketamine and xylazine is considered the most reliable for anesthesia of mice, despite that respiration was moderately decreased and the cardiovascular system was strongly depressed (Erhardt et al 1984). With the use of combined simultaneous in vivo intracellular and extracellular recording techniques, it was observed that ketamine/xylazine anesthesia induced slow oscillations (in local field potentials in the olfactory bulb and piriform cortex as well as in pyramidal cell membrane potentials in the piriform cortex) that are correlated with the natural breathing cycle of the rat and therefore appear to be directly related to ongoing periodic patterns of afferent input linked to respiration (Fontanini et al 2003).…”
Section: Effect Of the Preparation On Firing Synchronicitymentioning
confidence: 99%